Exploring the Factors Influencing Employees’ Turnover Intent: A Study into Electronic Manufacturing MNCs - Li, Daqing (2012)
With the development of Malaysian Economy, many employees tend to leave their current job in different industries. Employees’ turnover intent is as one of the important issues existing in different industry fields which restricted the inside development of big organizations. In recent years, more and more multinational cooperation have experienced the loss of many skilled people and educators due to the some factors, like benefits and compensation, training and development and supervision and etc. In this research, the main factors have been contributed to analyze the reason of employees’ turnover intent in Malaysia electronic manufacturing MNCs. These factors are job performance, job satisfaction, management supervision & style, and pay and promotion opportunity. Besides that, the proposed research framework is designed in order to better understanding of identifying variables towards employees’ turnover intent. In this research, the author will analyze the main 4 factors which influence employees’ turnover intent in electronic manufacturing MNCs in Klang Valley. The relationship between each factor with employees’ turnover intent will be determined in the finding and discussions based on the analysis of finding results. The research ends with empirical contributions as well as suggestions for organizations and HR managers, conclusion based on survey results to determine the relationship between each factor with employees’ turnover intent. Personal reflections will be present for future researchers.